Advances in Marine Chitin and Chitosan - David Harding (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Recently, biomass-based polymers from renewable resources have received increasing focus owing to the depletion of petroleum resources. Natural polysaccharides such as cellulose, hemicellulose, and starch are among the candidates from natural resources for biomass polysaccharide products including bioplastics. Although several kinds of neutral or anionic polysaccharides such as chitin, alginic acid, hyaluronic acid, heparin, and chondroitin sulfate exist in nature, natural cationic polysaccharides are quite limited. Chitin is second only to cellulose as the most natural abundant polysaccharide in the world. Chitosan, the product from the N-deacetylatation of chitin, appears to be the only natural cationic polysaccharide. Therefore, chitin and chitosan due to their unique properties are expected to continue to offer a vast number of possible applications for not only chemical or industrial use, but also biomedicine. The research history on chitins, one of the most major and abundant natural polysaccharides on earth, started around 1970. Since the 1980s, chitin and chitosan research (including D-glucosamine, N-acetyl-D-glucosamine, and their oligomers) has progressed significantly over several stages in both fundamental research and industrial fields.